Generalized Pairwise Comparisons for Survival Analysis - Fukuda, Musashi; Oba, Koji; Sakamaki, Kentaro (Journal of the Japan Statistical Society, Japanese Issue, 2023)
The Net Benefit and the Win Ratio are the effect measures used in clinical trials with survival endpoints such as oncology and cardiology. These measures are based on generalized pairwise comparisons. In a randomized trial, the statistical methods estimate the ‘win’ probability that a subject randomly selected from the new treatment group has a better outcome than a subject from the control group and the ‘loss’ probability in the opposite situation. The Net Benefit is the difference between these probabilities, and the Win Ratio is the ratio between them. In this study, we review several estimators of the win/loss probability in terms of generalized pairwise comparisons, and the variance of those estimators based on U-statistic theory. Especially, we explain how to deal with the censored data to estimate those probabilities. Finally, we illustrate using the actual data to implement those statistical methods by R-packages.